Positive Legislature dalam Putusan Mahkamah Konstitusi Mengenai Upaya Hukum Putusan Penundaan Kewajiban Pembayaran Utang - Catur Alfath Satriya (The Constitutional Court of the Republic of Indonesia, 2022)
Constitutional Court as negative legislature as time goes by has become positive legislature, recently Constitutional Court verdict Number 23/PUU-XIX/2021 regarding Articel 235 examination from Bankruptcy Law and Debt Payment Postponement (PKPU) toward Indonesia’s Constitution (UUD NRI 1945), considered to cause constitutional losses because it does not regulate the existence of legal remedies against the PKPU verdict. This research aims to analyze the Judges consideration (ratio decidendi) of the Constitutional Court’s verdict regarding the legal remedies of PKPU verdict in accordance with the principles of justice and legal certainty and to analyze the enforcement of the Constitutional Court verdict regarding the legal remedies for the PKPU verdict which are positive legislation. This article used normative legal research method. The results of the study show that the progressivity in constructing the legal remedies in PKPU verdict with certain conditions (Conditionally Unconstitutional). The Constitutional Court’s decision which is final and binding in its implementation is not in accordance with the theory. It should be realized that in a decision that is self-executing, it still requires bureaucratic procedures to address the decision so that it can be implemented consistently in accordance with the principle of erga omnes.